Headache in Sickle Cell Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The prevalence of frequent headache in children with sickle cell disease (SCD) compared to that of control subjects without known sickle cell trait, and the cause of the headaches were studied at the Children's Hospital of Philadelphia, PA, and Duke University Medical Center.